A multi-platform approach to marine environment assessment in the Civitavecchia (Rome) area. (12th February 2016) - Zappalà, G.; Caruso, G.; Bonamano, S.; Madonia, A.; Piermattei, V.; Martellucci, R.; Di Cicco, A.; Pannocchi, A.; Stefanì, C.; Borsellino, C.; Marcelli, M.
ABSTRACT: Multi-platform systems for coastal environment monitoring are important tools that enable a better understanding of the dynamics of coastal ecosystems and their forcings; these observation networks can be used to highlight changes in marine ecosystems in response to anthropogenic impacts, identifying specific evolution. trends. This paper reports the results of a field study conducted in summer 2012 to test the efficacy of the multi-platform Civitavecchia Coastal Environment Monitoring System (C-CEMS). An observation programme was employed to analyse the fate of the Escherichia coli ( E. coli ) in bathing areas, to predict its dynamics and to prevent the sanitary risk associated with the presence of this microorganism in seawater.